The Effects of Work-Life Balance, Workload, Motivation, and Leadership Style on Driver Performance - Azizah, Ana Chosiatul; Anggraeni, Erike; Anita, Siska Yuli (Universitas Pamulang, 2026)
This study aims to analyze the influence of work-life balance, workload, work motivation, and leadership style on the performance of PT Berkah Bersama OJESA drivers from a Human Resource Management (HRMS) perspective. The background of this study stems from the need for sharia transportation companies to manage human resources effectively while still paying attention to work welfare and Islamic values ​​in special services for women. This study employed a quantitative approach with a survey method, distributing questionnaires to 34 active drivers at PT Berkah Bersama OJESA. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the aid of SmartPLS 4 software. The results showed that workload significantly impacted driver performance. This finding indicates that the workload assigned to drivers is at a level that encourages productivity and focus, resulting in optimal performance. Meanwhile, work-life balance, work motivation, and leadership style did not significantly influence driver performance. This indicates that these variables are not yet the dominant factors influencing driver performance at PT Berkah Bersama OJESA, both due to relatively homogeneous driver perceptions and job characteristics that are more influenced by operational factors than psychological and leadership factors. This research provides theoretical contributions to the study of MSDI, particularly in organizations based on Islamic values, and provides practical implications for the management of PT Berkah Bersama OJESA in formulating more effective human resource management strategies to improve driver performance.